EMOTIONAL INTELLIGENCE AND SERVICE QUALITY OF FACILITATORS’ INDONESIA HUMAN RESOURCES DEVELOPMENT AGENCY (HRDA) - Shine Pintor; Hety Budiyanti (Universitas Padjadjaran, 2021)
The model which was widely known and describes the concept of service quality is the Service Quality (SERVQUAL) model proposed by Parasuraman et al (1985). However, this model has a limitation, because its application merely for service providers in the business sector, not for service providers in the public sector and service providers in the education sector. In education sector, facilitators are always involved in interpersonal interaction with the training participants. Some researchers agree to uncover the relationship between the emotional intelligence of service providers and service quality. Based on the literature review, there are limited studies in the field of education and training of the Civil Service Apparatus, especially regarding the relationship between emotional intelligence and service quality. Thus, this study aims to reveal the effect of facilitators’ emotional intelligence on service quality with respondents from participants of Basic Education and Training (Diklatsar), Leadership Education and Training 3 (Diklatpim 3), and Leadership and Education Training 4 (Diklatpim 4) at HRDA Province. This study uses quantitative methods. The sample size in this study was 462 people who were collected through a survey with a purposive sampling technique. The data analysis technique used is SEM through a two-stage approach. The results showed that the facilitators’ emotional intelligence of HRDA of Central Java, East Java, West Java, Jakarta, Banten, Central Sulawesi, and North Sumatera Provinces, had a significant positive effect on the quality of service with social awareness as the indicator with the highest effect.